Evaluasi Kinerja STP Berdasarkan Parameter Kualitas dan Debit Buangan Limbah Domestik di PT PLN Nusantara Power UP Gresik - Putri Aprillia Wijayanti; Yayok Suryo Purnomo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to evaluate the performance of the Sewage Treatment Plant (STP) at PT PLN Nusantara Power Unit Pembangkitan Gresik in reducing pollutant loads from domestic wastewater. The evaluation involves analyzing water quality parameters including pH, BOD, COD, TSS, oil and grease, total ammonia, and total coliform at both inlet and outlet of the STP. Additionally, the actual daily discharge was observed and compared to the design capacity to assess operational efficiency. The method used was descriptive qualitative, involving field observation, documentation, and laboratory test data analysis during the January–March 2025 period. The results show that all outlet parameters met the effluent standards set by Regulation No. 68/2016 of the Ministry of Environment and Forestry. However, the actual flow rate, which is only 1.6–3.3% of the design capacity, indicates potential inefficiencies in energy use and biological processes. Therefore, operational adjustments and optimization of STP capacity utilization are necessary for more efficient and sustainable system performance.